Base of tongue as an unusual site for Non Hodgkin Lymphoma - Chenthilnathan, P; Mohamad, I; Razini, I; Samarendra, M (Bangladesh Journal of Medical Science, 2012)
Background: Non Hodgkin Lymphoma (NHL) has about 3-7% of oral manifestation. Most of the lesions are from the palate, gingival, tongue, buccal mucosa, floor of the mouth and lips. These site consist approximately 2% of all extra nodal lymphomas as primary origin. The prognosis of NHL depends to the tumour stage, tumour aggressiveness and their response to treatment. The oral lesions appear to respond quite well to irradiation or chemo radiation. Methods: We present a case of a 68 year-old Malay male presented with symptoms of voice change, poor oral intake and bleeding from oral cavity, which turns out to be NHL of the base of tongue without visceral involvement. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11740 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12